Characterization of pioglitazone cyclodextrin complexes: Molecular modeling to in vivo evaluation - Dinesh M Bramhane; Preethi A Kulkarni; Elvis A.F Martis; Raghuvir R. S Pissurlenkar; Evans C Coutinho; Mangal S Nagarsenker (Wolters Kluwer Medknow Publications, 2016)
Aims: The objective of present study was to study the influence of different β-cyclodextrin derivatives and different methods of complexation on aqueous solubility and consequent translation in in vivo performance of Pioglitazone (PE). Material and Methods: Three cyclodextrins: β-cyclodextrin (BCD), hydroxypropyl-β-cyclodextrin (HPBCD) and Sulfobutylether-7-β-cyclodextrin (SBEBCD) were employed in preparation of 1:1 Pioglitazone complexes by three methods viz. co-grinding, kneading and co-evaporation. Complexation was confirmed by phase solubility, proton NMR, Fourier Transform Infrared spectroscopy, Differential Scanning Calorimetry (DSC) and X-Ray diffraction (XRD). Mode of complexation was investigated by molecular dynamic studies. Pharmacodynamic study of blood glucose lowering activity of PE complexes was performed in Alloxan induced diabetic rat model. Results: Aqueous solubility of PE was significantly improved in presence of cyclodextrin. Apparent solubility constants were observed to be 254.33 M-1 for BCD-PE, 737.48 M-1 for HPBCD-PE and 5959.06 M-1 for SBEBCD-PE. The in silico predictions of mode of inclusion were in close agreement with the experimental proton NMR observation. DSC and XRD demonstrated complete amorphization of crystalline PE upon inclusion. All complexes exhibited >95% dissolution within 10 min compared to drug powder that showed <40% at the same time. Marked lowering of blood glucose was recorded for all complexes. Conclusion: Complexation of PE with different BCD significantly influenced its aqueous solubility, improved in vitro dissolution and consequently translated into enhanced pharmacodynamic activity in rats